Battery current collector and its manufacturing method, secondary battery, battery module, battery pack and power consumption device
Patent Information
- Application Number
- JP2022567171
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-10-29
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2041-10-29
Smart Images

Figure 0007624016000003 
Figure 0007624016000004 
Figure 0007624016000005
Abstract
Description
[Technical field]
[0001] The present application relates to a battery technology field, and in particular to a battery current collector and its manufacturing method, a secondary battery, a battery module, a battery pack and a power consuming device. [Background technology]
[0002] With the ever-increasing demand for energy and the ever-increasing awareness of environmental protection, new energy sources are increasingly being attached to people's attention.
[0003] Secondary batteries are a common new energy source, and current collectors are an important component of secondary batteries, and current collectors not only support active materials, but also collect electrons from electrochemical reactions and lead them to an external circuit, thereby realizing the process of converting chemical energy into electrical energy. The mechanical performance of the current collector made of metal foam is relatively poor, so when the current collector made of metal foam is used as a negative electrode current collector, the punched tab or spin-welded tab has low strength and is easily broken, which causes other problems. Summary of the Invention [Problem to be solved by the invention]
[0004] The present application provides a battery current collector and a manufacturing method thereof, a secondary battery, a battery module, a battery pack, and a power consumption device, for improving the problem in related art that the mechanical performance of a current collector made of a foam metal material is poor. [Means for solving the problem]
[0005] According to one aspect of the present application, a battery current collector for use in a single battery is provided. The battery current collector includes a metal foam layer and a strength reinforcing layer, which is a sheet metal layer, and the strength reinforcing layer and the metal foam layer are laminated and metallurgically bonded to each other, thereby solving the problem in the related art of poor mechanical performance of the current collector. The strength reinforcing layer and the metal foam layer are connected by a metallurgical bonding method, and atoms are bonded by mutual diffusion between the interface between the strength reinforcing layer and the metal foam layer. Therefore, the metallurgically bonded connection method is not only advantageous in ensuring the structural strength of the strength reinforcing layer and the metal foam layer, but also advantageous in ensuring the realization of good electrical conductivity between the strength reinforcing layer and the metal foam layer. Furthermore, the adoption of the metallurgically bonded method is also advantageous in reducing manufacturing costs.
[0006] In some embodiments, the metal foam layer and the strength reinforcing layer are welded together, which has the advantages of simple processing and high production efficiency.
[0007] In some embodiments, the foam metal layer and the strength reinforcing layer are sintered together, and the material and parameters of the current collector can be controlled by controlling the components of the metal powder or the mixing ratio of different powders (e.g., the porosity can be controlled by controlling the proportion of the pore-forming agent), which is advantageous for adjusting the performance parameters of the current collector according to actual needs. In addition, the foam metal layer and the strength reinforcing layer are sintered together, which is advantageous for reducing the residual stress generated in the connection process, thereby ensuring that the current collector will not crack during the winding process.
[0008] In some embodiments, the foam metal layer includes a first foam metal layer provided on one side of the strength reinforcement layer and a second foam metal layer provided on the other side of the strength reinforcement layer, so that the current collector meets the characteristics of a symmetrical electrode structure.
[0009] In some embodiments, the strength reinforcing layer has through holes so that the battery fluid on both sides of the strength reinforcing layer can flow to each other.
[0010] In some embodiments, the battery current collector includes a current collector body and an end portion for forming a tab located on the outer side along the width direction of the current collector body, the current collector body includes a foam metal layer and a strength reinforcing layer which are laminated together, and the end portion includes the strength reinforcing layer, thereby ensuring the mechanical performance of the area of the current collector that forms the tab and avoiding defects that may occur when the tab located at one end of the current collector is welded to the conductive part.
[0011] In some embodiments, the strength reinforcing layer is flush with the foam metal layer at both ends in the width direction, and the end of the current collector for forming the tab has the strength reinforcing layer, thereby ensuring the mechanical performance of the area of the current collector for forming the tab and avoiding defects that may occur when the tab located at one end of the current collector is welded to the conductive part.
[0012] In some embodiments, one end of the strength reinforcement layer protrudes from the foam metal layer in the width direction and the other end is flush with the foam metal layer, and the strength reinforcement layer constituting the tab is left at one end of the current collector, which is advantageous for simplifying the processing steps of the battery and improving production efficiency.
[0013] The strength reinforcing layer has both ends protruding from the foam metal layer in the width direction, and the strength reinforcing layer constituting the tab is left on both ends of the current collector, which is advantageous for simplifying the processing steps of the battery and improving production efficiency. Furthermore, the strength reinforcing layer constituting the tab is left on both ends of the current collector, which can expand the options for post-processing.
[0014] In some embodiments, the material of the foam metal layer is at least one of copper, nickel, aluminum, iron, magnesium, titanium, steel, and alloys, and the material of the strength reinforcement layer is at least one of copper, nickel, aluminum, iron, magnesium, titanium, steel, and alloys, thereby providing the current collector with good bending resistance and ease of bending, and facilitating winding of the current collector into a roll.
[0015] In some embodiments, the thickness of the metal foam layer is 10 to 100 μm and the thickness of the strength reinforcement layer is 4 to 12 μm, which can ensure sufficient contact between the metal foam layer and the active material of the battery while also ensuring good bending resistance of the current collector.
[0016] In some embodiments, the porosity of the foam metal layer is 20% to 90%, and optionally the porosity of the foam metal layer 1 is 80% to 85%. While ensuring sufficient contact between the foam metal layer and the active material of the battery, it is also possible to ensure good bending resistance of the current collector.
[0017] According to another aspect of the present application, a method for manufacturing the above battery current collector is further provided. The manufacturing method includes a material pressing step and a sintering step, in which the material pressing step includes laying a first layer of material for forming a metal foam layer and pressing the first layer of material, and laying a second layer of material for forming a strength reinforcing layer on the billet of the first layer and pressing the second layer of material into the billet of the second layer, the second layer of material including a metal powder. The sintering step includes sintering the material after pressing formed in the material pressing step. By controlling the components of the metal powder or the blending ratio of different powders, the material and parameters of the current collector can be controlled (for example, the porosity can be controlled by controlling the proportion of the pore-forming agent), which is advantageous for adjusting the performance parameters of the current collector according to actual needs. In addition, the sintering molding of the metal foam layer and the strength reinforcing layer is also advantageous for reducing the residual stress generated in the connection process, thereby ensuring that the current collector does not crack in the winding process.
[0018] In some embodiments, the material pressing step further includes laying a third layer material on the second layer billet to form a foam metal layer, and pressing the third layer material onto the third layer billet, where the third layer material includes a metal powder and a pore-forming agent mixed in the metal powder, so that the current collector meets the characteristics of a symmetrical electrode structure.
[0019] In some embodiments, the pressing pressure of the material of the first layer is less than or equal to the pressing pressure of the material of the third layer, which is advantageous for matching performance parameters of the first and second metal foam layers.
[0020] In some embodiments, the pressing pressure of the first layer material is 150-350 MPa, and the pressing pressure of the third layer material is 150-350 MPa.
[0021] In some embodiments, the material is in a protective atmosphere of inert gas during sintering to prevent the metal powder from oxidizing during the sintering process, and / or the sintering temperature of the material is 700-1000° C., and / or the sintering time of the material is 5-8 hours.
[0022] According to another aspect of the present application, a method for manufacturing the above battery current collector is further provided. The method includes a welding step and a foaming step. The welding step includes stacking an alloy foil sheet for forming a metal foam layer and a metal foil sheet for forming a strength reinforcing layer, and heating the alloy foil sheet and the metal foil sheet to weld them together to form an intermediate body. The foaming step includes putting the intermediate body into a corrosive solution to remove one or more elements of the alloy foil sheet to form the alloy foil sheet into a metal foam layer. The metal foam layer and the strength reinforcing layer are welded, which has the advantages of a simple processing process and high production efficiency.
[0023] In some embodiments, in the welding step, the metal foil sheet is laminated with an alloy foil sheet on each side thereof, so that the current collector meets the characteristics of a symmetrical electrode structure.
[0024] In some embodiments, the corrosive solution comprises at least one of a dilute hydrochloric acid solution, an ammonium sulfate solution, an electrolyte solution of H2SO4 and MnSO4, an acetic acid solution, a phosphoric acid solution, and a sulfuric acid solution, and / or the alloy foil sheet comprises a brass foil sheet, and / or the metal foil sheet comprises a pure copper foil sheet.
[0025] In some embodiments, before stacking the alloy foil sheet and the metal foil sheet, a plurality of through holes are formed on the metal foil sheet to allow the battery fluid on both sides of the strength reinforcing layer to flow to each other.
[0026] According to another aspect of the present application, there is further provided a secondary battery, which includes the battery current collector described above or a battery current collector manufactured by the manufacturing method described above.
[0027] According to another aspect of the present application, there is further provided a battery module, the battery module including the above-mentioned secondary battery.
[0028] According to another aspect of the present application, there is further provided a battery pack, the battery pack including the above-mentioned secondary battery.
[0029] According to another aspect of the present application, there is further provided a power consuming device, the power consuming device including at least one selected from the above secondary battery, the above battery module, or the above battery pack. [Brief description of the drawings]
[0030] In order to more clearly describe the technical solutions of the embodiments of the present application, the following briefly introduces the necessary accompanying drawings used in the embodiments of the present application. It is obvious that the accompanying drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other accompanying drawings based on the accompanying drawings without exerting creative efforts. [Figure 1] FIG. 2 is a structural schematic diagram of a battery current collector according to one alternative embodiment of the present application. [Diagram 2] FIG. 2 is a structural schematic diagram of a battery current collector according to another optional embodiment of the present application. [Diagram 3] FIG. 2 is a structural schematic diagram of a battery current collector according to another optional embodiment of the present application. [Figure 4] 1 is a schematic diagram of a secondary battery according to an embodiment of the present application. [Diagram 5] FIG. 5 is an exploded view of the secondary battery according to the embodiment of the present application shown in FIG. 4. [Figure 6] FIG. 1 is a schematic diagram of a battery module according to an embodiment of the present application. [Figure 7] FIG. 2 is a diagram illustrating the principle of a tab pull force test in an embodiment of the present application.
[0031] In the accompanying drawings, the drawings are not drawn to scale. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0032] The embodiments of the present application are described in more detail below in conjunction with the drawings and examples. The detailed description of the following examples and drawings are for illustrative purposes of the principles of the present application, but cannot be used to limit the scope of the present application, i.e., the present application is not limited to the described examples.
[0033] In the description of this specification, it should be explained that unless otherwise specified, "multiple" means two or more, and the orientation or positional relationship indicated by terms such as "upper", "lower", "left", "right", "inner", "outer", etc., is merely for facilitating and simplifying the description of this application, and does not indicate or suggest that the indicated device or element has a particular orientation and must be configured and operated in a particular orientation, and should not be understood as limiting this application. Furthermore, terms such as "first", "second", "third", etc. are merely for description, and should not be understood as indicating or suggesting relative importance. "Perpendicular" is not strictly perpendicular, but has a margin of error. "Parallel" is not strictly parallel, but has a margin of error.
[0034] All directional terms appearing in the following description are directions shown in the drawings, and do not limit the specific structure of the present application. In the description of the present application, it should be further explained that unless otherwise specified and limited, the terms "attached", "connected" and "connected" should be understood in a broad sense, for example, may be fixedly connected, detachably connected, or integrally connected, may be directly connected, or may be indirectly connected via an intermediate medium. For those skilled in the art, the specific meaning of the above terms in the present application may be understood according to the specific situation.
[0035] The "ranges" disclosed in this application are defined in the form of lower and upper limits, and a given range is defined by selecting one lower limit and one upper limit that define the boundaries of the particular range. Such defined ranges may or may not include the end values and may be arbitrarily combined, i.e., any lower limit and any upper limit may be combined to form a range. For example, if the ranges 60-120 and 80-110 are listed for a particular parameter, it is understood that the ranges 60-110 and 80-120 are also contemplated. However, if the minimum range values listed are 1 and 2, and the maximum range values listed are 3, 4, and 5, then all of the ranges 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5 are contemplated. In this application, unless otherwise stated, the numerical range "a-b" represents a shorthand expression representing any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed herein, and "0-5" is merely a shorthand for combinations of these numbers. Also, when a parameter is described as an integer ≧2, this is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0036] Unless otherwise stated, all the embodiments and optional embodiments in the present application may be combined with each other to form a new technical solution.
[0037] Unless otherwise stated, all technical features and optional technical features in the present application may be combined with each other to form a new technical solution.
[0038] Unless otherwise stated, all steps in the application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b) to mean that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method further includes step (c) as mentioned above to mean that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0039] Unless otherwise specified, the terms "comprise" and "comprises" referred to in this application may be open ended or closed ended. For example, the terms "comprise" and "comprises" may further include or include other ingredients not listed, or may include or include only the listed ingredients.
[0040] In this application, unless otherwise stated, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, any of the following conditions satisfy "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) but B is true (or exists); and A and B are both true (or exist).
[0041] As shown in Figures 1 to 3, in order to improve the problem in the related art that breakage is likely to occur when punching out a tab at the end of the current collector or welding the tab of the battery current collector to a conductive part, the battery current collector of this embodiment includes a foam metal layer 1 and a strength reinforcing layer 2 laminated on the foam metal layer 1.
[0042] The base of the foam metal layer 1 has a large number of communicating or non-communicating pores, thereby allowing the base of the foam metal layer 1 to be in sufficient contact with the active material of the battery.
[0043] The strength reinforcing layer 2 is a sheet-like metal layer. The sheet-like metal layer in this application refers to a sheet-like structure of a metal material with no internal pores and a non-foamed structure. It should be noted that the non-foamed structure with no internal pores may have through holes or surface depressions. The battery current collector of this embodiment includes a strength reinforcing layer 2, which improves the problem in the related art that the mechanical performance of the current collector is poor.
[0044] In this embodiment, the strength reinforcing layer 2 and the foam metal layer are metallurgically bonded. Being metallurgically bonded is a bond formed by mutual diffusion of atoms between the interfaces of two metal parts, and this bond or connection state is formed by the action of temperature and / or pressure. The strength reinforcing layer 2 and the foam metal layer 1 are connected by a metallurgical bonding method, and the atoms are bonded by mutual diffusion between the interfaces of the strength reinforcing layer and the foam metal layer. Compared with other joining methods such as adhesion, the metallurgically bonded connection method is not only advantageous in ensuring the structural strength of the strength reinforcing layer 2 and the foam metal layer 1, but also advantageous in ensuring the realization of good conductive performance between the strength reinforcing layer 2 and the foam metal layer 1, and further, adopting the metallurgically bonded method is also advantageous in reducing manufacturing costs.
[0045] In some embodiments, the strength reinforcing layer 2 is made of copper or copper-based material, which not only enhances the mechanical performance of the current collector, but also provides the current collector with good weldability and electrical conductivity, and is advantageous in ensuring the bending resistance of the current collector and preventing breakage during the process of winding the current collector into a roll. The strength reinforcing layer 2 can also be made of other materials with excellent strength, electrical conductivity, and plastic toughness, such as nickel, aluminum, iron, magnesium, titanium, steel, and alloys.
[0046] In some embodiments, the foamed metal layer 1 includes foamed copper. The foamed copper has good electrical conductivity, which is advantageous for reducing the internal resistance of the battery, and the foamed copper also has good bending resistance, so as to avoid breakage during the process of winding the current collector into a roll. The foamed metal layer 1 can also select other materials with good electrical conductivity and plastic toughness, such as nickel, aluminum, iron, magnesium, titanium, steel and alloys.
[0047] In some embodiments, the metal foam layer 1 and the strength reinforcing layer 2 are welded together. The current collector is formed by welding an alloy foil sheet for forming the metal foam layer 1 and a metal foil sheet for forming the strength reinforcing layer 2 together. In this embodiment, the current collector is formed by welding two types of foil material, an alloy foil sheet and a metal foil sheet, which has the advantages of a simple processing process and high production efficiency.
[0048] In some other embodiments, the foam metal layer 1 and the strength reinforcing layer 2 are sintered together. The foam metal layer 1 and the strength reinforcing layer 2 are sintered by different metal powders, and the foam metal layer 1 and the strength reinforcing layer 2 are bonded together by sintering. In the production process, the material and parameters of the current collector can be controlled by controlling the components of the metal powders or the blending ratio of different powders (for example, the porosity can be controlled by controlling the proportion of the pore-forming agent), which is advantageous for adjusting the performance parameters of the current collector according to actual needs. In addition, the sintering of the foam metal layer 1 and the strength reinforcing layer 2 is also advantageous for reducing the residual stress generated in the connection process, thereby ensuring that the current collector will not crack in the winding process.
[0049] In some embodiments, the foam metal layer 1 includes a first foam metal layer 11 provided on one side of the strength reinforcement layer 2 and a second foam metal layer 12 provided on the other side of the strength reinforcement layer 2, so that the current collector meets the characteristics of a symmetrical electrode structure.
[0050] A through hole is provided in the strength reinforcing layer 2 so that the battery fluid on both sides of the strength reinforcing layer 2 can flow to each other.
[0051] The battery current collector includes a current collector body and an end portion for forming a tab, the end portion including a strength reinforcing layer 2 and a foam metal layer 1 which are stacked together, thereby ensuring the mechanical performance of the area of the current collector which forms the tab and avoiding defects which may occur when the tab located at one end of the current collector is welded to a conductive part.
[0052] As shown in FIG. 1, in some optional embodiments of the present application, the strength reinforcing layer 2 is flush with the foam metal layer 1 at both ends in the width direction, and the end of the current collector for forming the tab has the strength reinforcing layer 2, thereby ensuring the mechanical performance of the area of the current collector for forming the tab and avoiding defects that may occur when the tab located at one end of the current collector is welded to the conductive part.
[0053] As shown in FIG. 2, in some other optional embodiments of the present application, one end of the strength reinforcement layer 2 protrudes from the foam metal layer 1 in the width direction and the other end is flush with the foam metal layer 1, and the portion of the strength reinforcement layer 2 protruding from the foam metal layer 1 is used to form a tab of the current collector. The strength reinforcement layer 2 constituting the tab is left at one end of the current collector, which is advantageous for simplifying the processing steps of the battery and improving production efficiency.
[0054] As shown in Fig. 3, in some other selectable embodiments of the present application, the strength reinforcing layer 2 has both ends protruding from the foam metal layer 1 in the width direction, and the strength reinforcing layer 2 constituting the tab is left on both ends of the current collector, which is advantageous for simplifying the processing steps of the battery and improving production efficiency. Furthermore, the strength reinforcing layer 2 constituting the tab is left on both ends of the current collector, which can expand the options for post-processing.
[0055] In some embodiments, the thickness of the foam metal layer 1 is 10 to 100 μm. If the thickness of the foam metal layer 1 is too small, the number of pores in the foam metal layer 1 is also small, and the contact surface between the foam metal layer 1 and the active material in the battery is also small. If the thickness of the foam metal layer 1 is too large, the bending resistance of the foam metal layer 1 is reduced, and breakage is likely to occur in the process of winding the current collector into a roll. The thickness of the foam metal layer 1 is 10 to 100 μm, which can ensure sufficient contact between the foam metal layer 1 and the active material of the battery while also ensuring good bending resistance of the current collector.
[0056] In some embodiments, the thickness of the strength reinforcing layer 2 is 4 to 12 μm. The thicker the strength reinforcing layer 2, the better the mechanical performance of the current collector, but the easier it is to bend the current collector, which makes it difficult to wind the current collector into a roll. The thickness of the strength reinforcing layer 2 is 4 to 12 μm, which ensures good mechanical performance of the current collector while also ensuring good ease of bending of the current collector.
[0057] In some embodiments, the porosity of the foam metal layer 1 is 20%-90%. The porosity is the ratio of the volume of the pores inside a porous solid material to the total volume of the material. The larger the porosity of the foam metal layer 1, the larger the contact area between the foam metal layer 1 and the active material of the battery. However, the corresponding bending resistance of the foam metal layer 1 is reduced, and breakage is likely to occur in the process of winding the current collector into a roll. The porosity of the foam metal layer 1 is 20%-90%, which can ensure sufficient contact between the foam metal layer 1 and the active material of the battery while also ensuring good bending resistance of the current collector.
[0058] In some other embodiments, the porosity of the metal foam layer 1 is 80%-85%, and the volumetric energy density of a battery using a battery current collector having a porosity of 80%-85% of the metal foam layer 1 is high, and the porosity can be improved from 20% to 80% or 85%, and the mass energy density can be improved by about 58%. According to another aspect of the present application, there is further provided a manufacturing method for the above battery current collector, which includes a material pressing step and a sintering step.
[0059] The material pressing step includes laying a first layer of material for forming a foam metal layer 1, pressing the first layer of material into a first layer billet, the first layer of material including a metal powder and a pore-forming agent mixed with the metal powder, and laying a second layer of material for forming a strength reinforcement layer 2 on the first layer billet, pressing the second layer of material into the second layer billet, the second layer of material including a metal powder.
[0060] The sintering step includes sintering the pressed material formed in the material pressing step.
[0061] The foam metal layer 1 and the strength reinforcing layer 2 are sintered together. The foam metal layer 1 and the strength reinforcing layer 2 are sintered with different metal powders, and the foam metal layer 1 and the strength reinforcing layer 2 are bonded together by sintering. In the production process, the material and parameters of the current collector can be controlled by controlling the components of the metal powders or the blending ratio of different powders (for example, the porosity of the foam metal layer 1), which is advantageous for adjusting the performance parameters of the current collector according to actual needs. In addition, the sintering of the foam metal layer 1 and the strength reinforcing layer 2 is also advantageous for reducing the residual stress generated in the connection process, thereby ensuring that the current collector will not crack in the winding process.
[0062] In some embodiments, the pore-forming agent has a particle size of 0.1-0.7 mm, and the metal powder has a particle size of 0.05-0.1 mm. In some embodiments, the metal powder is copper powder. In some embodiments, the pore-forming agent is a soluble salt or a high-temperature decomposable salt, and the pore-forming agent may be NaCl or urea.
[0063] The manufacturing method further includes a material preparation step before the material pressing step. The material preparation step includes material preparation of a first material layer, which includes sieving the pore-forming agent particles into particles with different particle sizes and uniformly mixing the metal powder and the pore-forming agent. In this embodiment, the pore-forming agent particles may be spherical or nearly spherical in shape, and the pore-forming agent particles having an average particle size of 0.1 to 0.7 mm are obtained by sieving.
[0064] Among these, uniformly mixing the metal powder and the pore-forming agent includes uniformly mixing pure copper powder having a particle size of 0.05 to 0.1 mm with pore-forming agent particles having the above particle size, in which the volume ratio of the pure copper powder to the pore-forming agent particles having the above particle size is 1:9 to 8:2, and then adding an appropriate amount of organic solvent and stirring for about 0.4 to 1 hour to form a mixed powder.
[0065] The material preparation step includes preparing a material for a second material layer, and the material preparation for the second material layer includes uniformly mixing a metal powder and an organic solvent.
[0066] Wherein, the material pressing step further includes laying a third layer material on the second layer billet to form a foam metal layer 1, and pressing the third layer material onto the third layer billet, the third layer material including a metal powder and a pore-forming agent mixed in the metal powder. In some embodiments, the material of the third material layer is the same as the material of the first material layer.
[0067] Among them, the thickness of the first layer billet is the same as that of the third layer billet. The thickness of the first layer billet is 10 to 100 μm. The thickness of the second layer billet is 4 to 12 μm.
[0068] Wherein, the pressing pressure of the first layer material is equal to or lower than the pressing pressure of the third layer material, and since the first layer material is pressed multiple times, the pressing pressure of the first layer material is equal to or lower than the pressing pressure of the third layer material, which is advantageous for matching the performance parameters of the first metal foam layer 11 and the second metal foam layer 12. In some embodiments, at least one of the pressing pressure of the first layer material and the pressing pressure of the third layer material is 100-350 MPa.
[0069] During sintering, the material is in a protective atmosphere of inert gas to prevent the metal powder from oxidizing during the sintering process. In some embodiments, the inert gas comprises argon gas.
[0070] Specifically, the sintering step includes placing the multi-layer billet in a protective atmosphere and sintering it in a sintering furnace at 700-1000°C for 5-8 hours, and thoroughly washing the sintered and water-cooled samples with running deionized water and absolute ethanol to obtain the final product.
[0071] FIG. 1 shows a battery current collector of this embodiment manufactured using the above manufacturing method. Both sides of the strength reinforcing layer 2 of this battery current collector are a first metal foam layer 11 and a second metal foam layer 12, respectively. The strength reinforcing layer 2 is a pure copper layer, and the porosity of both the first metal foam layer 11 and the second metal foam layer 12 is 35% to 40%, and both have a thickness of 40 to 50 μm. The thickness of the strength reinforcing layer 2 is 5 to 6 μm. Both ends of the strength reinforcing layer 2 and the metal foam layer 1 are flush with each other in the width direction.
[0072] In some embodiments, the pore-forming agent particles may be spherical or near-spherical in shape, so that the pores formed in the first metal foam layer 11 and the second metal foam layer 12 in this embodiment may be circular or near-circular in shape, closed pores, or through pores. In some embodiments, the pores are uniformly distributed in the first metal foam layer 11 and the second metal foam layer 12.
[0073] According to another aspect of the present application, there is further provided another method for manufacturing the above battery current collector, which includes a welding step and a foaming step.
[0074] The welding step includes stacking an alloy foil sheet for forming the metal foam layer 1 and a metal foil sheet for forming the strength reinforcing layer 2, and heating the alloy foil sheet and the metal foil sheet to weld them together to form an intermediate body. The foaming step includes putting the intermediate body into a corrosive solution to remove one or more elements in the alloy foil sheet to form the alloy foil sheet into the metal foam layer 1. The current collector is formed by welding two types of foil materials, the alloy foil sheet and the metal foil sheet, and has the advantages of a simple processing process and high production efficiency.
[0075] In some embodiments, the corrosive solution comprises a dilute hydrochloric acid solution, the alloy foil sheet comprises a brass foil sheet, and the metal foil sheet comprises a pure copper foil sheet.
[0076] In some other embodiments, the corrosive solution includes one of an ammonium sulfate solution, an electrolyte mixture of H2SO4 and MnSO4, an acetic acid solution, a phosphoric acid solution, and a sulfuric acid solution.
[0077] In the welding step, alloy foil sheets are stacked on both sides of the metal foil sheet respectively to ensure that the current collector meets the characteristics of a symmetrical electrode structure.
[0078] The manufacturing method further includes a cutting step before the welding step, in which the cutting step includes cutting the alloy foil sheet and the metal foil sheet into a pre-made material of a predetermined width. In this embodiment, by making the widths of the alloy foil sheet and the metal foil sheet the same, the foam metal layer 1 and the strength reinforcing layer 2 can easily form a current collector whose both ends in the width direction are flush with each other. In some other embodiments, by making the width of the alloy foil sheet smaller than the width of the metal foil sheet, the strength reinforcing layer 2 can easily form a current collector whose one or both ends in the width direction protrude from the foam metal layer 1.
[0079] The method further includes a cleaning step of cleaning the surfaces of the alloy foil sheet and the metal foil sheet before the welding step. In some embodiments, the cleaning step is after the cutting step, to prevent cross-contamination of the foil sheets during the cutting step.
[0080] Specifically, the cleaning step includes immersing the alloy foil sheet and the metal foil sheet in an anhydrous ethanol solution to perform a cleaning process to remove dust and metal particles on the foil material surface, and then putting the alloy foil sheet and the metal foil sheet into an air box to air dry.
[0081] Specifically, the welding step includes laminating the cleaned foil sheet in the order of an alloy foil sheet, a metal foil sheet, and an alloy foil sheet, and then sintering the laminated foil sheets in a sintering furnace at a temperature of 700 to 920°C to weld the multi-layer foil sheet, and the sintering time is in accordance with the fusion of the contact surfaces of the alloy foil sheet and the metal foil sheet. Lamination refers to completely overlapping the width of the foil sheets or shifting the ends in the width direction.
[0082] Specifically, the foaming step includes immersing the welded multi-layer foil sheet in a dilute hydrochloric acid solution to remove the zinc element in the brass.
[0083] The manufacturing method further includes a washing step after the foaming step, specifically, the washing step includes placing the material obtained in the foaming step in clean water and performing ultrasonic treatment to remove ions adsorbed on the surface to obtain the final current collector.
[0084] The manufacturing method further includes forming a plurality of through holes on the metal foil sheet before stacking the alloy foil sheet and the metal foil sheet, to allow the battery fluids on both sides of the strength reinforcing layer 2 to flow to each other.
[0085] FIG. 2 shows a battery current collector according to one embodiment of the present application, which is manufactured using the above manufacturing method. Both sides of the strength reinforcing layer 2 of this battery current collector are a first metal foam layer 11 and a second metal foam layer 12, respectively. The strength reinforcing layer 2 is a pure copper layer, and the porosity of both the first metal foam layer 11 and the second metal foam layer 12 is 35% to 40%, and both have a thickness of 40 to 50 μm. The thickness of the strength reinforcing layer 2 is 5 to 6 μm. One end of the strength reinforcing layer 2 protrudes from the metal foam layer 1 in the width direction.
[0086] FIG. 3 shows a battery current collector according to one embodiment of the present application, which is manufactured using the above manufacturing method. Both sides of the strength reinforcing layer 2 of this battery current collector are a first metal foam layer 11 and a second metal foam layer 12. The strength reinforcing layer 2 is a pure copper layer, and the first metal foam layer 11 and the second metal foam layer 12 both have a porosity of 45% to 50%, and both have a thickness of 30 to 40 μm. The strength reinforcing layer 2 has a thickness of 5 to 6 μm. Both ends of the strength reinforcing layer 2 protrude from the metal foam layer 1 in the width direction.
[0087] The secondary battery, battery module, battery pack and power consuming device of the present application will be described below with appropriate reference to the accompanying drawings.
[0088] In one embodiment of the present application, a secondary battery is provided.
[0089] Generally, a secondary battery includes a positive electrode plate, a negative electrode plate, an electrolyte, and a separator. During the charging and discharging process of the battery, active ions shuttle between the positive electrode plate and the negative electrode plate to absorb and release. The electrolyte serves to conduct ions between the positive electrode plate and the negative electrode plate. The separator is provided between the positive electrode plate and the negative electrode plate, and mainly serves to prevent short-circuiting between the positive and negative electrodes, while allowing ions to pass through.
[0090] [Positive electrode plate] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer provided on at least one surface of the positive electrode current collector, the positive electrode film layer including the positive electrode active material of the first aspect of the present application.
[0091] For example, the positive electrode current collector has two surfaces opposing each other in the thickness direction of the positive electrode current collector, and the positive electrode film layer is laminated on either one or both of the two opposing surfaces of the positive electrode current collector.
[0092] In some embodiments, the positive electrode current collector is a battery current collector described above or a battery current collector produced by the battery current collector production method described above.
[0093] In some of the other embodiments, the positive electrode current collector can be a metal foil sheet or a composite current collector. For example, the metal foil sheet can be an aluminum foil. The composite current collector can include a polymeric base layer and a metal layer formed on at least one surface of the polymeric substrate. The composite current collector can be formed by forming a metal material (such as aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymeric substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0094] In some embodiments, the positive electrode active material may be a positive electrode active material for batteries known in the art. Exemplarily, the positive electrode active material may include at least one of lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and modified compounds thereof. However, the present application is not limited to these materials, and other conventional materials that can be used as a battery positive electrode active material may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides include lithium cobalt oxide (e.g., LiCoO2), lithium nickel oxide (e.g., LiNiO2), lithium manganese oxide (e.g., LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel manganese oxide (LiNi 1 / 3 Co1 / 3 Mn 1 / 3 O2 (may be abbreviated as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (may be abbreviated as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (may be abbreviated as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (may be abbreviated as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (which may be abbreviated as NCM811), lithium nickel cobalt aluminum oxide (e.g. LiNi 0.85 Co 0.15 Al 0.05 Examples of the lithium-containing phosphate having an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (e.g., LiFePO4 (which may be abbreviated as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (e.g., LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, and a composite material of lithium manganese iron phosphate and carbon.
[0095] In some embodiments, the positive electrode membrane layer further optionally includes an adhesive. Exemplarily, the adhesive may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0096] In some embodiments, the positive electrode membrane layer further optionally includes a conductive agent. Exemplarily, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0097] In some embodiments, the positive electrode plate can be manufactured by the following method: The above-mentioned components for manufacturing the positive electrode plate, such as the positive electrode active material, the conductive agent, the adhesive, and any other components, are dispersed in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry, and the positive electrode slurry is applied onto a positive electrode current collector, and the positive electrode plate can be obtained through processes such as drying and cold pressing.
[0098] [Negative electrode plate] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, the negative electrode film layer including a negative electrode active material.
[0099] For example, the negative electrode current collector has two surfaces opposing each other in the thickness direction of the negative electrode current collector, and the negative electrode film layer is laminated on either one or both of the two opposing surfaces of the negative electrode current collector.
[0100] In some embodiments, the negative electrode current collector is a battery current collector described above or a battery current collector produced by the battery current collector production method described above.
[0101] In some embodiments, the negative electrode active material may be a negative electrode active material for a battery known in the art. Exemplarily, the negative electrode active material may include at least one of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based material, tin-based material, and lithium titanate. The silicon-based material may be selected from at least one of silicon alone, silicon oxide, silicon carbon composite, silicon nitrogen composite, and silicon alloy. The tin-based material may be selected from at least one of tin alone, tin oxide, and tin alloy. However, the present application is not limited to these materials, and other conventional materials that can be used as a battery negative electrode active material may be used. These negative electrode active materials may be used alone or in combination of two or more types.
[0102] In some embodiments, the negative electrode membrane layer further optionally includes an adhesive, which may be selected from at least one of styrene butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0103] In some embodiments, the negative electrode membrane layer further optionally includes a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0104] In some embodiments, the negative electrode membrane layer further optionally contains other auxiliary agents, such as a thickening agent (eg, sodium carboxymethylcellulose (CMC-Na)).
[0105] In some embodiments, the negative electrode plate can be manufactured by the following method: The above-mentioned components for manufacturing the negative electrode plate, such as the negative electrode active material, the conductive agent, the adhesive, and any other components, are dispersed in a solvent (e.g., deionized water) to form a negative electrode slurry, and the negative electrode slurry is applied onto a negative electrode current collector, and the negative electrode plate can be obtained through processes such as drying and cold pressing.
[0106] [Electrolyte] The electrolyte serves to conduct ions between the positive and negative electrodes. The present application does not specifically limit the type of electrolyte, and it can be selected according to needs. For example, the electrolyte may be liquid, gel, or all solid.
[0107] In some embodiments, the electrolyte employs an electrolyte solution, the electrolyte solution including an electrolyte salt and a solvent.
[0108] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluoro(oxalato)borate, lithium bis(oxalato)borate, lithium difluorobis(oxalato)phosphate, and lithium tetrafluoro(oxalato)phosphate.
[0109] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfone, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.
[0110] In some embodiments, the electrolyte solution further optionally includes additives. For example, the additives may include a negative electrode film-forming additive, a positive electrode film-forming additive, or an additive that can improve some performance of the battery, such as an additive that improves the overcharge performance of the battery, or an additive that improves the high-temperature or low-temperature performance of the battery.
[0111] [Separator] In some embodiments, the secondary battery further includes a separator. The present application does not particularly limit the type of separator, and any well-known separator with a porous structure having good chemical stability and mechanical stability may be selected.
[0112] In some embodiments, the material of the separator may be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single-layer thin film or a multi-layer composite thin film, and there is no particular limitation. When the separator is a multi-layer composite thin film, the materials of each layer may be the same or different, and there is no particular limitation.
[0113] In some embodiments, the positive and negative plates and the separator can be manufactured into an electrode component by a winding or lamination process.
[0114] In some embodiments, the secondary battery may include an exterior body, which may be used to package the electrode components and the electrolyte.
[0115] In some embodiments, the exterior of the secondary battery may be a hard case, such as a hard plastic case, an aluminum case, a steel case, etc. The exterior of the secondary battery may be a soft bag, such as a pouch-type soft bag. The material of the soft bag may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0116] The present application does not particularly limit the shape of the secondary battery, which may be cylindrical, rectangular or any other shape. For example, FIG. 4 shows a secondary battery 5 with a rectangular structure as an example.
[0117] In some embodiments, referring to FIG. 5, the exterior body may include a housing 51 and a cover plate 53. The housing 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate surround and form a receiving chamber. The housing 51 has an opening communicating with the receiving chamber, and the cover plate 53 can be installed on the opening to close the receiving chamber. The positive electrode plate, the negative electrode plate and the separator can form an electrode component 52 by a winding process or a lamination process. The electrode component 52 is packaged in the receiving chamber. The electrolyte is immersed in the electrode component 52. The number of electrode components 52 included in the secondary battery 5 may be one or more, and may be selected by those skilled in the art according to actual specific needs.
[0118] In some embodiments, the secondary batteries may be assembled into a battery module, and the number of secondary batteries included in the battery module may be one or more, with the specific number being selectable by one skilled in the art based on the application and capacity of the battery module.
[0119] Fig. 6 shows an example of a battery module 4. Referring to Fig. 6, in the battery module 4, the multiple secondary batteries 5 may be arranged in order along the length direction of the battery module 4. Of course, they may be arranged in any other manner. Furthermore, the multiple secondary batteries 5 may be fixed by a fastener.
[0120] Optionally, the battery module 4 may further include a housing having an accommodating space, and the multiple secondary batteries 5 are accommodated in the accommodating space.
[0121] In some embodiments, the battery modules may be further assembled into a battery pack, and the number of battery modules included in the battery pack may be one or more, and the specific number may be selected by one skilled in the art based on the application and capacity of the battery pack.
[0122] The following table shows the experimental data of the battery current collector using the technical means of this embodiment and the battery current collector of the comparative example. The examples described below are illustrative and are used only to interpret this application, and should not be understood as limiting this application. In the examples, specific techniques or conditions are not specified, but are carried out according to the techniques or conditions described in the technical literature or product instructions. Reagents or equipment used without the manufacturer specified are all general products that can be purchased commercially.
[0123] The parameters and performance tests of the battery current collectors of the examples and comparative examples are as shown in the table below.
[0124] [Table 1]
[0125] [Table 2]
[0126] Conductivity is a parameter that represents the conductive performance of a material. The higher the conductivity, the better the conductivity of the material. Among them, conductivity σ = 1 / resistivity ρ, and resistivity is obtained by measuring with a resistivity meter.
[0127] Resistivity test method: The test sample is embedded between the two electrodes of the resistivity meter and they are in good contact. The ratio of the DC voltage applied to both electrodes to the current flowing within the volume of the sample is called the volume resistance Rv. The resistance between the two opposing surfaces of 1 cm of material calculated from Rv, the electrodes and the sample size is called the volume resistivity ρv. That is, ρv=Rv*S / d(Ω / cm), where S is the area of the measuring electrode, d is the thickness of the sample and Rv is the volume resistivity.
[0128] Tab shear tensile test method: As shown in Figure 7, the welded sample (formed by welding the adapter sheet 7 and the foil material 8) is clamped, and the upper and lower clamps clamp the adapter sheet 7 and the foil material 8 (battery current collector) respectively, and both clamps are on the same line in the horizontal or vertical direction, and the force receiving direction and the plane of the welded print are kept vertically parallel, so that the tab cannot be torn when clamped. The upper and lower clamps move relative to each other at a speed of 30 mm / min to pull the sample, and the tensile force when the sample breaks is the tab weld shear tensile.
[0129] The volumetric energy density test method includes manufacturing a secondary battery and measuring the volumetric energy density of the secondary battery.
[0130] The method for producing the secondary battery is as follows.
[0131] 1. NCM811 is used as the positive electrode active material, and the conductive agent acetylene black and adhesive polyvinylidene fluoride (PVDF) are thoroughly mixed and homogenized in a mass ratio of 94:3:3 in an N-methylpyrrolidone solvent system. The mixture is then applied to an aluminum foil, dried, and cold pressed to obtain a positive electrode plate.
[0132] 2. The negative electrode active material, artificial graphite, the conductive agent, acetylene black, the adhesive, styrene butadiene rubber (SBR), and the thickener, sodium carboxymethylcellulose (CMC), are thoroughly mixed and homogenized in a deionized water solvent system in a mass ratio of 90:5:2:2:1, and then coated on the current collectors in the above examples and comparative examples, dried, and cold pressed to obtain the negative electrode plate.
[0133] 3. A porous polymeric thin film made of polyethylene (PE) is used as the separator.
[0134] 4. The positive electrode plate, separator and negative electrode plate are stacked in order, the separator is placed between the positive and negative electrodes to provide isolation, and then wound to obtain a bare cell. The bare cell is placed in an outer casing, and 1M lithium hexafluorophosphate (solvent: 20% vol ethylene carbonate, 30% dimethyl carbonate, and 50% methyl ethyl carbonate) electrolyte is injected and packaged to obtain a secondary battery.
[0135] The method for measuring the volumetric energy density of a secondary battery is as follows.
[0136] 1. Each secondary battery manufactured above is allowed to stand for 5 minutes in a constant temperature environment of 25°C, then discharged to 2.8V at 1 / 3C, allowed to stand for 5 minutes again, charged to 4.2V at 1 / 3C, then charged at a constant voltage of 4.2V to a current of 0.05C or less, allowed to stand for 5 minutes again, and the charge capacity at this time is C0, and then discharged to 2.8V at 1 / 3C, and the discharge capacity at this time is the initial discharge capacity and is D0.
[0137] 2. Multiply the tested discharge capacity value (initial discharge capacity D0) by the system platform voltage U and divide it by the battery housing volume V to obtain the volumetric energy density of the battery.
[0138] The manufacturing process of Comparative Example 1 is as follows.
[0139] 1. As a pore-forming agent, commercially available NaCl salt balls in the form of beads (purity ≧99%) are used and sieved, and a sieve with an average particle size of 0.1 mm is selected as a reserve.
[0140] 2. The NaCl particles with an average particle size of 0.1 mm obtained after processing and sieving in step 1, commercially available electrolytic copper powder (purity ≧99.5%), and ethanol are uniformly mixed, then placed in a press mold and pressed in one direction up to 200 MPa to obtain a green body. The masses of the electrolytic copper powder and NaCl particles are 1792 g and 1728 g, respectively, and the amount of ethanol added relative to the total mass of the electrolytic copper powder and NaCl is 70.4 g.
[0141] 3. Place the green body obtained in step 2 in an argon gas atmosphere and sinter it in a sintering furnace at 740°C for 3 hours, then increase the temperature to 920°C and sinter it for 5 hours.
[0142] 4. The article obtained in step 3 is cooled together with the furnace to room temperature, and the skin of the article is removed by wire cutting. Then, the article is placed in circulating hot water to dissolve the NaCl particles until the mass of the article does not change. The article is then washed in an ultrasonic water bath for 15 minutes, washed with acetone, and dried in an oven at 80°C to obtain a porous copper foam with a porosity of 80%.
[0143] The manufacturing process of Comparative Example 2 is as follows.
[0144] 1. As a pore-forming agent, commercially available NaCl salt balls in the form of beads (purity ≧99%) are used and sieved, and a sieve with an average particle size of 0.1 mm is selected as a reserve.
[0145] 2. The NaCl particles with an average particle size of 0.1 mm obtained through processing and sieving in step 1, commercially available electrolytic copper powder (purity ≧99.5%) and ethanol are uniformly mixed, then placed in a press mold and pressed in one direction up to 200 MPa to obtain a green body. The masses of the electrolytic copper powder and NaCl particles are 1792 g and 1728 g, respectively, and the amount of ethanol added relative to the total mass of the electrolytic copper powder and NaCl is 70.4 g.
[0146] 3. Place the green body obtained in step 2 in an argon gas atmosphere and sinter it in a sintering furnace at 740°C for 3 hours, then increase the temperature to 920°C and sinter it for 5 hours.
[0147] 4. The article obtained in step 3 is cooled together with the furnace to room temperature, and the skin of the article is removed by wire cutting, then placed in circulating hot water to dissolve the NaCl particles, and washed in an ultrasonic water bath for 15 minutes until the mass of the article does not change, and then washed with acetone and dried in an oven at 80°C to obtain a porous copper foam with a porosity of 80%.
[0148] 5. Take two of the porous copper foams obtained in step 4, and apply a commercially available conductive carbon adhesive (DAG-T-502 adhesive, manufactured by TED PELLA, INC., USA, specification 30g / bottle) evenly to a thickness of 10um on one surface of one of the porous copper foams, and then bond the two outer porous copper foams together to obtain a conductive adhesive-bonded copper foam.
[0149] The manufacturing process of Example 1 is as follows.
[0150] 1. As a pore-forming agent, commercially available NaCl salt balls in the form of beads (purity ≧99%) are used and sieved, and a sieve with an average particle size of 0.1 mm is selected as a reserve.
[0151] 2. The NaCl particles with an average particle size of 0.1 mm obtained through processing and sieving in step 1, commercially available electrolytic copper powder (purity ≧99.5%), and 2% ethanol based on the total mass of the electrolytic copper powder and NaCl are uniformly mixed, then placed in a press mold and pressed in one direction up to 200 Mpa to obtain a first layer of a green body. A mixture of electrolytic copper powder and ethanol is tiled on the first layer, and pressed in one direction up to 200 Mpa to obtain a second layer of a green body, and a mixture of NaCl particles, commercially available electrolytic copper powder, and ethanol is tiled on the second layer, and pressed in one direction up to 200 Mpa to obtain a third layer of a green body. The masses of the electrolytic copper powder and NaCl particles are 1792 g and 1728 g, respectively, and the mass of ethanol is 70.4 g.
[0152] 3. Place the green body obtained in step 2 in an argon gas atmosphere and sinter it in a sintering furnace at 740°C for 3 hours, then increase the temperature to 920°C and sinter it for 5 hours.
[0153] 4. The article obtained in step 3 is cooled together with the furnace to room temperature, the skin of the article is removed by wire cutting, then the article is placed in circulating hot water to dissolve the NaCl particles until the mass of the article does not change, the article is placed in an ultrasonic water bath to wash for 15 minutes, washed with acetone, and then dried in an oven at 80°C to obtain porous foamed copper. The porosity of the current collector in Example 1 is 80%.
[0154] The manufacturing process of Example 2 is as follows.
[0155] 1. As a pore-forming agent, commercially available NaCl salt balls in the form of beads (purity ≧99%) are used and sieved, and a sieve with an average particle size of 0.1 mm is selected as a reserve.
[0156] 2. The NaCl particles with an average particle size of 0.1 mm obtained through the processing and sieving in step 1, commercially available electrolytic copper powder (purity ≧99.5%), and 2% ethanol based on the total mass of the electrolytic copper powder and NaCl are uniformly mixed, then placed in a press mold and pressed in one direction up to 200 Mpa to obtain a first layer of a green body. A mixture of electrolytic copper powder and ethanol is tiled on the first layer, and pressed in one direction up to 200 Mpa to obtain a second layer of a green body, and a mixture of NaCl particles, commercially available electrolytic copper powder, and ethanol is tiled on the second layer, and pressed in one direction up to 200 Mpa to obtain a third layer of a green body. The masses of the electrolytic copper powder and NaCl particles are 1344 g and 1836 g, respectively, and the mass of ethanol is 63.6 g.
[0157] 3. Place the green body obtained in step 2 in an argon gas atmosphere and sinter it in a sintering furnace at 740°C for 3 hours, then increase the temperature to 920°C and sinter it for 5 hours.
[0158] 4. The article obtained in step 3 is cooled together with the furnace to room temperature, the skin of the article is removed by wire cutting, then the article is placed in circulating hot water to dissolve the NaCl particles until the mass of the article does not change, the article is placed in an ultrasonic water bath to wash for 15 minutes, washed with acetone, and then dried in an oven at 80°C to obtain porous foamed copper. The porosity of the current collector in Example 2 is 85%.
[0159] Although the present application has been described in conjunction with the preferred embodiments, various improvements can be made thereto and the parts therein can be replaced with equivalents without departing from the scope of the present application. In particular, the technical features mentioned in each embodiment can be combined in any manner, as long as there is no structural contradiction. The present application is not limited to the specific embodiments disclosed in the present specification, but includes all technical solutions within the scope of the claims. [Explanation of symbols]
[0160] 1. Foam metal layer 11 First foam metal layer 12 Second foam metal layer 2 Strengthening layer 4 Battery Module 5 Secondary battery 51 Housing 52 Electrode Components 53 Lid plate 6 Clamp 7 Adapter sheet 8 Foil material
Claims
1. A method for manufacturing a battery current collector, comprising the steps of: a material pressing step including laying a first layer material for forming a foam metal layer (1) and pressing the first layer material onto a billet for the first layer, the first layer material including a metal powder and a pore-forming agent mixed with the metal powder; and laying a second layer material for forming a strength reinforcing layer (2) on the billet for the first layer and pressing the second layer material onto the billet for the second layer, the second layer material including a metal powder; and a sintering step including sintering the pressed material formed in the material pressing step.
2. 2. The manufacturing method according to claim 1, wherein the material pressing step further includes laying a third layer material for forming the foam metal layer (1) on the billet of the second layer, and pressing the third layer material onto the billet of the third layer, the third layer material including a metal powder and a pore-forming agent mixed with the metal powder.
3. The method of claim 2 , wherein a pressing pressure of the material of the first layer is equal to or less than a pressing pressure of the material of the third layer.
4. The pressing pressure of the material of the first layer is 150 to 350 MPa; The method according to claim 2 or 3, wherein the pressing pressure of the material of the third layer is 150 to 350 MPa.
5. the material is in a protective atmosphere of inert gas during sintering; and / or The sintering temperature of the material is between 700 and 1000°C, and / or The method according to any one of claims 1 to 4, wherein the sintering time of the material is between 5 and 8 hours.
6. A manufacturing method described in any one of claims 1 to 5, wherein the particle size of the pore-forming agent is 0.1 to 0.7 mm and the particle size of the metal powder is 0.05 to 0.1 mm.
7. A manufacturing method described in any one of claims 1 to 6, wherein the metal powder is copper powder.
8. A method for manufacturing a battery current collector, comprising the steps of: a welding step including stacking an alloy foil sheet for forming a foam metal layer (1) and a metal foil sheet for forming a strength reinforcing layer (2) and heating the alloy foil sheet and the metal foil sheet to weld them together to form an intermediate body; and a foaming step including removing one or more elements of the alloy foil sheet by placing the intermediate in a corrosive solution to form the alloy foil sheet into the foam metal layer (1).
9. The manufacturing method according to claim 8 , wherein in the welding step, the alloy foil sheet is stacked on both sides of the metal foil sheet.
10. The corrosive solution is a dilute hydrochloric acid solution, an ammonium sulfate solution, a H 2 SO 4 and MnSO 4 and / or the electrolyte solution includes at least one of an acetic acid solution, a phosphoric acid solution, and a sulfuric acid solution. The alloy foil sheet comprises a brass foil sheet; and / or The method of claim 8 or 9, wherein the metal foil sheet comprises a pure copper foil sheet.
11. The method according to claim 8 , further comprising forming a plurality of through holes in the metal foil sheet before stacking the alloy foil sheet and the metal foil sheet.
12. Use of the method according to any one of claims 1 to 11 in the manufacture of a secondary battery.
13. Use of the manufacturing method according to any one of claims 1 to 11 in the manufacture of a battery module.
14. Use of the manufacturing method according to any one of claims 1 to 11 in the manufacture of a battery pack.
15. 12. Use of the method according to any one of claims 1 to 11 in the manufacture of an electrical power consuming device.
Citation Information
Patent Citations
Porous current collector and preparing method thereof
CN106159277A
Preparation method of metallic nickel porous material with controllable main pore diameter value gradient distribution
CN110947969A
Foam nickel with composite structure and manufacturing method thereof
CN1150339A
Laminate metal material at least containing a foam metal layer and its preparation method
CN1962256A
Bipolar porous polar plate-current collecting body
CN2588551Y